Coordinating a decentralized supply chain with capacity cost compensation - Shan, Feifei; Dai, Xiaopei; Men, Jinqi; Yang, Feng (R.A.I.R.O. Recherche opérationnelle, 2021)
Capacity planning, as a vital asset, is a challenge problem for firms in various industries, such as organic agriculture, apparels and high-tech industry. However, many manufacturers are conservative about their capacity investment for a variety of reasons. As a result, many retailers have the motivation to stimulate manufacturers to enhance the capacity level. In this paper, we propose a revenue sharing and capacity cost compensation contract to help the retailer stimulate her manufacturer to increase the capacity level. In the contract, the retailer keeps a portion of sales revenue and compensates for the manufacturer’s capacity cost. They face a stochastic demand and play a Stackelberg game where the retailer acts as a leader and the manufacturer acts as a follower. We prove that the channel can be perfectly coordinated through our proposed contract. Moreover, we give a feasible range of profit distribution, in which both channel members can earn no less profit than that in non-cooperation. Meanwhile, comparing with centralized channel with multiplicative demand, we find that capacity in decentralized channel tends to be lower.